2012
DOI: 10.1371/journal.pone.0032105
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Diversity in New Members of the Reticulocyte Binding Protein Family in Thai Plasmodium vivax Isolates

Abstract: Background Plasmodium vivax merozoites specifically invade reticulocytes. Until recently, two reticulocyte-binding proteins (Pvrbp1 and Pvrbp2) expressed at the apical pole of the P. vivax merozoite were considered to be involved in reticulocyte recognition. The genome sequence recently obtained for the Salvador I (Sal-I) strain of P. vivax revealed additional genes in this family, and in particular Pvrbp2a, Pvrbp2b (Pvrbp2 has been renamed as Pvrbp2c) and two pseudogenes Pvrbp2d and Pvrbp3. It had been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
0
23
0
3
Order By: Relevance
“…Previous analyses of several Pvrbp sequences have revealed evidence of positive diversifying selection ( 14 , 29 ). These studies found a strikingly high degree of polymorphism in Pvrbp2c relative to other Pvrbp genes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of several Pvrbp sequences have revealed evidence of positive diversifying selection ( 14 , 29 ). These studies found a strikingly high degree of polymorphism in Pvrbp2c relative to other Pvrbp genes.…”
Section: Discussionmentioning
confidence: 99%
“…A significant portion of malaria cases in Thailand occur among temporary migrant workers from bordering countries presenting a major challenge to prevention and control of malaria in Thailand. The genetic polymorphism in the Reticulocyte Binding Protein (RBP), Merozoite Surface Protein 5 (MSP-5) and Merozoite Surface Protein 3 α/β of P. vivax Thai isolates were analyzed in previous studies and showed high levels of genetic polymorphism (2326). However, the information on the nature and extent of population diversity as well as the antigenic character of malaria parasites in Thailand is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…RBL proteins feature a small and large exon separated by a small intron, and the small exon encodes the signal peptide [ 19 , 20 ]. The complete gene sequence of P. vivax Salvador I (Sal-1) strain comprises genes for 11 P. vivax reticulocyte binding proteins (PvRBP) as well as 2 pseudogenes [ 14 , 21 ]. Five of these genes are highly expressed in schizont stage during the erythrocytic stage of P. vivax parasites [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%